New approach for vitamin E extraction in rainbow trout flesh: Application in fish fed commercial and red seaweed‐supplemented diets. Issue 9 (29th June 2015) - Araújo, Mariana; Alves, Rita C.; Pimentel, Filipa B.; Costa, Anabela S.G.; Fernandes, Telmo J.R.; Valente, Luísa M.P.; Rema, Paulo; Oliveira, M. Beatriz P.P.
<x xml:space="preserve">Abstract</x> A vitamin E extraction method for rainbow trout flesh was optimized, validated, and applied in fish fed commercial and Gracilaria vermiculophylla‐supplemented diets. Five extraction methods were compared. Vitamers were analyzed by HPLC/DAD/fluorescence. A solid‐liquid extraction with n‐hexane, which showed the best performance, was optimized and validated. Among the eight vitamers, only α‐ and γ‐tocopherol were detected in muscle samples. The final method showed good linearity (>0.999), intra‐ (<3.1%) and inter‐day precision (<2.6%), and recoveries (>96%). Detection and quantification limits were 39.9 and 121.0 ng/g of muscle, for α‐tocopherol, and 111.4 ng/g and 337.6 ng/g, for γ‐tocopherol, respectively. Compared to the control group, the dietary inclusion of 5% G. vermiculophylla resulted in a slight reduction of lipids in muscle and, consequently, of α‐ and γ‐tocopherol. Nevertheless, vitamin E profile in lipids was maintained. In general, the results may be explained by the lower vitamin E level in seaweed‐containing diet. Practical Applications: Based on the validation results and the low solvent consumption, the developed method can be used to analyze vitamin E in rainbow trout. The results of this work are also a valuable information source for fish feed industries and aquaculture producers, which can focus on improving seaweed inclusion in feeds as a source of vitamin E in fish muscle and, therefore, take full advantage of all bioactive components with an important role in fish health and flesh quality. <inline-graphic xlink:href="ark:/27927/pgj2n17wtt8" content-type="ejlt201400656-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Muscle samples from rainbow trout fed a commercial diets were used to select, optimize, and validate an extraction method for vitamin E. The final method was used to extract α and γ‐tocopherol in muscle from rainbow trout fed a control (CTRL) and a seaweed‐supplemented diet (GRA).